Potencial role of salicylic acid in tolerance of maize to Fusarium graminearum - Szőke, Csaba (Acta Biologica Szegediensis, 2011)
Six maize genotypes were examined to reveal correlations between stalk rot caused by Fusarium graminearum and the levels of cellulase activity and endogenous salicylic acid. Our results showed that in resistant genotypes the cellulase activities are lower than in sensitive and moderately resistant genotypes. This suggests that determining the cellulase enzyme activity in stalk tissue could provide a good indication of the stalk rot resistance of the genotypes. It was also demonstrated that Fusarium infection affected differently the salicylic acid content in the six genotypes.